Occurrence of Viscum album subsp. album L. on Laburnum anagyroides Medik. in Toruń, Poland - Nienartowicz, Andrzej; Rutkowski, Lucjan; Kamiński, Dariusz; Kunz, Mieczysław (Ecological Questions, 2021)
This short note presents two localities of the common mistletoe growing on the common laburnum found in central Poland in the city of Toruń in 2020. The common laburnum is one of the rare hosts of this recently rapidly spreading semi-parasite. The presented relationship between the two species has so far been reported in only several publications, mostly from the late 19th and early 20th century.